Osteoporosis and periodontitis: a bidirectional relationship - Khinda, Paramjit Kaur (Brazilian Dental Science, 2017)
Osteoporosis is a condition of compromised bone strength that predisposes an individual to increased risk of fracture and is a major cause of morbidity in older susceptible individuals. Osteoporosis is related to various endocrinal abnormalities, metabolic and nutritional factors, postmenopausal hormonal changes and consumption of certain drugs such as cortisone. Emerging clinical and molecular evidence suggests that inflammation also exerts significant influence on osteoporotic bone changes. Numerous pro-inflammatory cytokines have been shown to be associated with regulation of osteoblast and osteoclast differentiation. Chronic inflammatory conditions causing immune system remodeling may serve as pathological risk factors for osteoporosis. The present article reviews the current perspective on the interaction between bone morphology and immune system in the inflammatory condition (periodontitis), unleashing the link between two chronic conditions.KeywordsOsteoporosis; Periodontitis; Inflammation; Bone remodelling.